Problematika Musyrif dalam Membentuk Karakter Mandiri Santri di Rumah Tahfizh Al ‘Arif - Huda, Abdullah Bill; Arsyad, Junaidi (Continuous Education: Journal of Science and Research, 2025)
The research conducted at the Al 'Arif Tahfizh House aims to explore in depth the role of a musyrif, the problems that occur and solutions in the formation of independent character of students. The research method used by the researcher is a qualitative research method with a case study approach. Research data was obtained using observation techniques, interviews, and document studies. Determination of research subjects using a non-probability sampling technique, namely by selecting research subjects randomly with the consideration of being able to represent the entire existing population. The results of this study are the role of musyrif as a role model for students, guiding students, caring for students, motivating students, facilitating students so they do not get bored, and conditioning students, and not being arrogant. The problems of musyrif in forming independent character of students at the Al 'Arif Tahfizh House are divided into two, namely internal and external problems. Internal problems of musyrif: musyrif does not provide an example to students, musyrif does not have basic counseling, lack of supervision from musyrif. As for the external problems are factors of students, factors of parents of students and environmental factors. The solutions offered to the students are to learn the basics of counseling, become a parental figure for the students, be more creative, collaborate with the students' parents, be selective in accepting students and provide independent learning.